ENHANCING THE SOCIAL AND RELIGIOUS CHARACTER OF STUDENTS AT QURRATU A'YUN HIGH SCHOOL THROUGH EXTRACURRICULAR ACTIVITIES - Hatta Fakhrurrozi; Masturah Minabari; Fatimah Saguni; Tri Marfiyanto (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
Religious education in schools is expected to have a significant impact on the development of students' religious and social character so as to prevent them from immoral social behavior. This research tries to identify extracurricular activities that help improve the social and religious character of students. This research uses qualitative methodologies, with in-depth interviews providing as data collecting technique. The data were subsequently analysed utilising triangulation techniques by modifying existing theories. According to the findings of this study, the school offers an Islamic tarbiyah programme as an extracurricular activity from Saturday through Sunday. Every day, a programme called tawjihat murabbiyat is used to control Islamic tarbiyah activities. In addition to extracurricular activities, the improvement of students' religious and social character is accomplished by the incorporation of religious principles into subject matter and the entrenching of appropriate behaviour in school culture. Developing social character involves working on a variety of skills, including discipline, respect for others, serving both parents, tolerance, humility, and caring for others and the environment. Concerning the religious attitudes fostered by the program, such as the practise of congregational prayer, the wearing of the veil, and become a Mutamayyiz Muslims.